2019
DOI: 10.1590/0102-311x00125518
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status throughout life and body mass index: a systematic review and meta-analysis

Abstract: This article aimed to systematically review the association between socioeconomic status according to the life course models and the body mass index (BMI) in adults. A review was performed following the guidelines of the PRISMA. The studies were identified in the MEDLINE/PubMed, LILACS and Web of Science databases. The eligible articles investigated the association between at least one life course model (risk accumulation, critical period or social mobility) and BMI. In order to assess the quality of the selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…We found some widening differences between stable low and high SEP groups among men from the younger birth cohort, but these differences were not greater at any age compared to the differences found among women. Our results support the strong evidence from previous studies where stable low SEP has been associated with higher BMI, particularly among women in high-income countries ( Newton et al, 2017 ; Vieira et al, 2019 ). Vulnerability to weight gain among constantly disadvantaged women has been explained, for example, by a greater stress response to social disadvantage and greater weight-related social and occupational discrimination compared to men ( Pudrovska et al, 2014 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We found some widening differences between stable low and high SEP groups among men from the younger birth cohort, but these differences were not greater at any age compared to the differences found among women. Our results support the strong evidence from previous studies where stable low SEP has been associated with higher BMI, particularly among women in high-income countries ( Newton et al, 2017 ; Vieira et al, 2019 ). Vulnerability to weight gain among constantly disadvantaged women has been explained, for example, by a greater stress response to social disadvantage and greater weight-related social and occupational discrimination compared to men ( Pudrovska et al, 2014 ).…”
Section: Discussionsupporting
confidence: 92%
“…Since the youngest participants were 40 years old in Phase 1, we can assume that most of the participants (and their parents) completed their highest education before the follow-up; thus, further social mobility after Phase 1 is not probable among the participants. Although different SEP measures are not interchangeable because they capture different aspects of SEP ( Braveman et al, 2005 ), the selection between education and occupation as an SEP measure in high-income Western countries has not substantially affected the findings of the SEP inequalities in BMI ( McLaren, 2007 ; Vieira et al, 2019 ). Education encompasses not only material aspects of SEP but also non-material aspects, such as knowledge, literacy, and cognitive capacity ( Braveman et al, 2005 ; Galobardes et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, a research with data of the adult Brazilian population has found that the prevalence of overweight and obesity increased in all levels of education between 2006 and 2013, while the increase in the prevalence of BMI >40 kg/m 2 was more significant in the higher level of education [32]. Another recent review and meta-analysis that aimed to assess the association between socioeconomic status and BMI in adults found a higher risk of overweight in women with low socioeconomic status [33], in line with the findings of our study.…”
Section: Discussionmentioning
confidence: 99%